Simulation of seasonally varying waves in the Manila Bay area using SWAN - Cadiz, Joshua Daniel N.
This study aims to use SWAN, a coastal wave model, in the simulation of the seasonal variation of wave climate of a section in the Manila Bay Area. The simulation requires input of wind, tidal, and bathymetric data which were obtained from government agencies. Additional software were used for preprocessing tidal and bathymetric data, and postprocessing data obtained from SWAN. A series of wave climate maps were generated, one for each month, and one for each season. The results of the simulation show that wave climate in the Bay is generally gentle. with significant wave heights typically not exceeding 1m in height throughout the bay. Wave climate differences due to seasonal variation of winds and tides were most notable in the upper left portion of the bay where wave heights tend to increase in the rainy season due to generally stronger winds.